2019
DOI: 10.1128/mra.00196-19
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence of Monascus purpureus GB-01, an Industrial Strain for Food Colorant Production

Abstract: We report the draft genome sequence of Monascus purpureus GB-01, an industrial strain used as a food colorant. De novo assembly of long reads resulted in 121 chromosomal contigs and 1 mitochondrial contig, and sequencing errors were corrected by paired-end short reads. This genome sequence will provide useful information for azaphilone pigments and mycotoxin citrinin biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Based on the LOV and MK BGCs in Table 3 , we compared twelve genomes of Monascus spp. including eight published genomes, M. purpureus YY-1, YJX-8, GB-01, HQ1, NRRL1596, and M. ruber FWB13, CBS127566, NRRL 1597 [ 29 , 30 , 31 , 32 ], and four genomes of M. pilosus sequenced in this study, and found that all genomes of four M. pilosus strains and three M. ruber strains contained the MK BGCs while there was no MK BGC in those of five M. purpureus strains. Total 9 or 10 genes named mkA-mkI were highly conserved in the LOV and MK BGCs ( Table 4 , Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the LOV and MK BGCs in Table 3 , we compared twelve genomes of Monascus spp. including eight published genomes, M. purpureus YY-1, YJX-8, GB-01, HQ1, NRRL1596, and M. ruber FWB13, CBS127566, NRRL 1597 [ 29 , 30 , 31 , 32 ], and four genomes of M. pilosus sequenced in this study, and found that all genomes of four M. pilosus strains and three M. ruber strains contained the MK BGCs while there was no MK BGC in those of five M. purpureus strains. Total 9 or 10 genes named mkA-mkI were highly conserved in the LOV and MK BGCs ( Table 4 , Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, no genome information of M. pilosus has been released, and few industrially applied strains of Monascus spp. are available on the genome [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The omics-based technologies comprising genomics ( 29 , 30 ), transcriptomics ( 30 34 ), and proteomics ( 34 ) have been used to identify metabolic mechanisms implicated in carbon starvation stress ( 30 ), exposure to blue light ( 35 ), gene knockout mutants of mga 1–3 ( 32 ), and transmembrane secretion of extracellular MPs ( 34 ) in Monascus strains. These approaches help to elucidate the regulatory mechanisms of MP synthesis and diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Kumagai et al reported the genome sequence information of the high pigment-producing M . purpureus GB-01 strain, with a genome size of 24.3 Mb and 121 chromosomal contigs [ 20 ]. Liu et al identified the key genes ( ERG4 A and ERG4 B) for ergosterol biosynthesis in M .…”
Section: Introductionmentioning
confidence: 99%